2017
DOI: 10.1186/s13071-017-2299-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of heartworm in dogs and cats of Madrid, Spain

Abstract: Background Dirofilaria immitis causes heartworm disease, a chronic and potentially fatal cardiopulmonary disease which mainly affects dogs and cats. It is present in most of Spain, due to favourable climatic factors. Madrid, located in the centre of the Iberian Peninsula, is the most highly populated city in the country. There is a lack of current data on canine heartworm and there are no published epidemiological data regarding feline heartworm in this region, therefore the aim of this study was to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 24 publications
8
25
0
Order By: Relevance
“…By habitat, prevalences were significantly lower in dogs living indoors. This agrees with previous studies carried out in vectorborne diseases (9,23,34). This result is understandable since indoor animals are more protected against the presence of vectors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By habitat, prevalences were significantly lower in dogs living indoors. This agrees with previous studies carried out in vectorborne diseases (9,23,34). This result is understandable since indoor animals are more protected against the presence of vectors.…”
Section: Discussionsupporting
confidence: 92%
“…When the results obtained for dirofilariosis were evaluated, it was observed that the prevalences obtained in this study maintain similar values with respect to the areas that had been evaluated in the last 5-6 years, such as Barcelona, Madrid, Salamanca, or the Canary Islands (7,8,34,35). However, regarding studies carried out more than 25 years ago, two phenomena can be observed: on the one hand, an increase in the prevalence in endemic areas in the south and east [i.e., Extremadura, Murcia, Valencian Community, Catalonia, Aragon; (36)(37)(38)(39)(40)] and, on the other hand, progressive increase in the prevalence of areas with little presence of the parasite, or very localized presence, as is the case of Galicia (9,36,41), Castilla y León (36,42), Castilla la Mancha (36,43), or the Balearic Islands (23).…”
Section: Discussionsupporting
confidence: 68%
“…Numerous species of Bartonella have been identified as pathogenic to humans while Bartonella vinsonii berkhoffii and Bartonella henselae are associated with clinical disease in dogs [ 21 ]. Dirofilariasis due to Dirofilaria immitis or Dirofilaria repens is another vector-borne disease transmitted by mosquitoes from the family Culicidae present in Europe [ 8 , 12 , 22 , 23 ] that can affect both animals and humans [ 24 ], causing cardiopulmonary or subcutaneous disease manifestations, respectively [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of Diro laria spp. in cats varies between 0% and 33% across Europe [10,31,52,[91][92][93][94][95][96][97][98][99]. There does not seem to be any data on prevalence in Germany, speci cally.…”
Section: Discussionmentioning
confidence: 98%